Detection of lymph node metastasis from osteosarcoma with 99mTc-MDP scintigra - Ilić, Daniela (Radiology and oncology (Ljubljana), 1999)
Osteosarcoma usually spreads via the blood stream, developing pulmonary and skeletal metastasis. Rarely, the disease spreads via the lymphatics. We are reporting a case when radionuclide bone imaging detects lymph node metastasis from osteosarcoma.
Keywords: Bone neoplasms; Child; Lymphatic metastasis; Osteosarcoma; Radionuclide imaging; Technetium tc 99m medronate